GOOD VILLAGE GOVERNANCE AND CONSTRAINT IN MANAGING VILLAGE FUNDS IN LOBALAIN DISTRICT, ROTE NDAO REGENCY - Maria M. Lino; Belandina Liliana Long; Delila Anggelina Nahak Seran (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this study is to analyze Good Village Governance in the management of Village Funds and to find the inhibiting factors of Good Village Governance in the management of Village Funds in Lobalain District, Rote Ndao Regency. Using a qualitative approach with descriptive methods. Data collection was carried out using interview, observation and documentation techniques to obtain a comprehensive understanding of the governance of village funds being implemented. Data analysis techniques include several stages including data condensation, data presentation and drawing conclusions and testing the validity of data through source triangulation. The theory usedreferring to Permendagri No. 20 of 2018 that village financial management includes planning, implementation, administration, reporting and accountability. As well as the theory of Haris Fause (2023) that Good Village Governance in village financial management through the principles of transparency, participation and accountability The theory of the results of the study shows that the Village in managing Village Funds starting from planning, implementation, administration, reporting and accountability with the principles of good village governance has been running but the participatory principle is still only limited to the planning and implementation stages but not at the reporting and accountability stages. The principle of transparency is still limited to village information boards and billboards so that only people who come to the village office know, the principle of accountability has not been running well because it is still often late in submitting reports. This is due to several limitations, namely the capacity of the apparatus which is still low both in management and mastery of IT as well as facilities and infrastructure which are also still minimal. Therefore, the village government needs to pay attention to increasing the capacity of village officials through skills and knowledge training, procurement of the necessary facilities and infrastructure, especially village information media so that the principles of transparency and accountability become better.